2016
DOI: 10.3390/molecules21121685
|View full text |Cite
|
Sign up to set email alerts
|

Black Crowberry (Empetrum nigrum L.) Flavonoids and Their Health Promoting Activity

Abstract: Nowadays, much research attention is focused on underutilized berry crops due to the high antioxidant activity of fruits. Black crowberry (Empetrum nigrum L.) represents an important source of flavonols (quercetin, rutin, myricetin, naringenin, naringin, morin, and kaempferol) and anthocyanins. The fruit components could be utilised as natural colourants or as a part of functional foods and, because of the high antioxidant activity, the berries of black crowberry can be used in the treatment of diseases accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 52 publications
(102 reference statements)
1
24
0
Order By: Relevance
“…It is also rich in different nutrients, some of which contribute to orosensory properties. Empetrum extract has been demonstrated to protect cells against H 2 O 2 -induced cell damage via antioxidant properties by scavenging reactive oxygen species and by enhancing antioxidant enzyme activities, and it displays anti-inflammatory and anticancer activity, and has a positive effect on lipid metabolism [201,202]. In addition, Empetrum nigrum ssp.…”
Section: 11b Biotic Edaphic and Nutritional Factors Influencingmentioning
confidence: 99%
“…It is also rich in different nutrients, some of which contribute to orosensory properties. Empetrum extract has been demonstrated to protect cells against H 2 O 2 -induced cell damage via antioxidant properties by scavenging reactive oxygen species and by enhancing antioxidant enzyme activities, and it displays anti-inflammatory and anticancer activity, and has a positive effect on lipid metabolism [201,202]. In addition, Empetrum nigrum ssp.…”
Section: 11b Biotic Edaphic and Nutritional Factors Influencingmentioning
confidence: 99%
“…In both cases, health benefits are associated with high amounts of secondary metabolites like polyphenols (flavonoids, anthocyanins, flavonols, and phenolic acids) . There is a wide range of health benefits, from antioxidant properties to anti‐inflammatory and anti‐hypertensive effects, cardioprotective effects, and blood glucose regulation . Several studies have reported that diet is a very promising path to prevent metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 There is a wide range of health benefits, from antioxidant properties to anti-inflammatory and anti-hypertensive effects, cardioprotective effects, and blood glucose regulation. 15,16 Several studies have reported that diet is a very promising path to prevent metabolic syndrome. It can even reverse the progression of type II diabetes, and is also very important for reducing pharmacological treatments in type-II diabetes patients.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Studies show that high amounts of antioxidants are present in the crowberry. 1,4,[5][6][7][8][9] The total concentration of antioxidant activity in the crowberry was reported to be similar to black currant and blackberry and greater than blueberry and raspberry. 1,10,12,13 In addition, studies show that the crowberry is a great source of anthocyanins with yields similar to the bilberry, which contains the highest amount of anthocyanin of eleven common berries examined.…”
Section: Introductionmentioning
confidence: 99%